2021
DOI: 10.1177/09544070211006517
|View full text |Cite
|
Sign up to set email alerts
|

Skyhook control strategy for vehicle suspensions based on the distribution of the operational conditions

Abstract: In this work, a novel distribution-based control strategy of semi-active vehicle suspensions is tested under different conditions. The novelty lies in the use of an appropriate threshold in the operational condition of the control algorithm, with which the operational conditions severity is quantified and the state of the damper is controlled according to the magnitude of the operational conditions and not their sign. The value of the threshold depends on the vibrations induced to the sprung mass by the road p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The TLS suspension's left and right SDDs are denoted as R 2 and R 3 , respectively, while the left and right WDDs are denoted as R 4 and R 5 , respectively. Equation (13) represents the PSOF PID active controller's fitness function, which is obtained by optimizing the sum of the IATE of…”
Section: Pso Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The TLS suspension's left and right SDDs are denoted as R 2 and R 3 , respectively, while the left and right WDDs are denoted as R 4 and R 5 , respectively. Equation (13) represents the PSOF PID active controller's fitness function, which is obtained by optimizing the sum of the IATE of…”
Section: Pso Algorithmmentioning
confidence: 99%
“…In recent years, semi-active and active control strategies for different suspension types have become increasingly mature, such as the Skyhook control, 13 the sliding mode control, 14 the neural network, 15 the fuzzy logic, 16 etc. The PID controller is widely used because of its simple operation, strong applicability, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the safety improving advantages as mentioned above, existing studies have already shown the energy saving potential of such vehicle platforms [22,23]. Moreover, these types of vehicle configurations enable various other benefits such as more DoF for vehicle dynamics control [24], faulttolerance [25] and motion comfort enhancement [26].…”
Section: Introductionmentioning
confidence: 99%